Peran Academic Self-Efficacy dan Perfeksionisme terhadap Psychological Well-Being pada Siswa Program Akselerasi - Altu Nurta Rifdah; Mimbar Oktaviana (Jurnal Ragam Pengabdian, 2026)
Accelerated students possess high academic abilities but face greater academic demands and psychological pressure due to shorter learning periods, which can affect their Psychological well-being. Previous studies indicate that these students are vulnerable to stress, anxiety, and socio-emotional adjustment difficulties. Accordingly, this study sought to investigate the relationship between Academic self-efficacy and Perfectionism in relation to the Psychological well-being of accelerated students. Academic self-efficacy denotes students’ beliefs about their ability to cope with academic demands, Perfectionism relates to setting high personal standards, and Psychological well-being reflects positive psychological functioning. This quantitative correlational study involved all ninth-grade accelerated students at SMP X, Sidoarjo Regency (N = 34), using saturated sampling. Data were collected using SEQ-C, CAPS-SF, and BSPWB-A instruments and analyzed with SPSS 25 using Pearson correlation and multiple linear regression. The results revealed a significant positive relationship between Academic self-efficacy and Psychological well-being (r = 0.517; p < 0.05) and an inverse relationship between Perfectionism and Psychological well-being (r = −0.373; p < 0.05). Simultaneously, both variables contributed 46% to Psychological well-being, indicating that strong Academic self-efficacy enhances well-being, while maladaptive Perfectionism may reduce it.